Do property rights and contract farming matter for rural development? Evidence from a large-scale investment in Ghana - Susanne Väth; Michael Kirk (Philipps-University Marburg, Faculty of Business Administration and Economics, 2014)
With the rising demand for agricultural land, land deals must be designed to benefit not only the investors but also the local population. This paper looks at two ways this might be done for farmers in the vicinity of a large-scale oil palm investment in Ghana: contract farming and secure property rights to land. We compare farmers to whom outgrower contracts were allocated, in a quasi-natural experiment, with independent oil palm growers. We find that property rights have a significantly positive effect on households' agricultural income, profit per acre, and perceived future security, but that while contract farming has a significantly positive effect on households' aggregated assets and perceived future security, its effect on agricultural income and profit per acre is significantly negative because of effort substitution, since outgrowers have a higher probability of engaging in non-farm business. The identified effects are highly significant and supported by robustness checks. We conclude that large-scale investment need not be to the disadvantage of the local population if it respects existing bundles of property rights and may be beneficial for those who participate in contract farming.
Keywords: D60; O17; Q13; 330; Contract farming; Property rights; Large-scale land investment; Quasi-natural experiment; Oil palm; Ghana